Single-Lead Abnormal ECG Screening with a Lightweight Deep Learning Model for Wearable Health Monitoring - Ribeiro, Estela; Soares, Quenaz Bezerra; Almeida, Douglas de Andrade de; Jatene, Fabio; Gutierrez, Marco Antonio (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.20274, 2026)
Electrocardiograms (ECGs) are essential for cardiac assessment, and the rising adoption of wearables has intensified the need for automated identification of abnormal ECGs on resource-constrained platforms. We evaluate LiteVGG-11, a lightweight CNN (20,365 parameters), for binary classification using Lead II signals. The model was trained on CODE15 and validated on PTB-XL and real-world wearable data, achieving AUCs of 0.736 and 0.773, respectively. Wearable validation revealed a decline in specificity due to artifacts and Lead II’s spatial constraints. Findings indicate that LiteVGG-11 is feasible for preliminary screening in continuous health monitoring, despite limitations in identifying non-specific abnormalities that require multi-lead observation.